Anorectal melanoma - histopathological and immunohistochemical features and treatment - Cruz,Geraldo Magela Gomes da (2014)
Anorectal melanomas should be characterized by location (anal, rectal and anorectal), color, size, shape and mobility and microscopically, by melanocyte subtypes, grade of melanin pigmentation, junctional changes in the squamous epithelium, atypical mitotic index, cellular atypia, inflammatory infiltrate, vascular and perineural invasion, sentinel lymph node, and anorectal parietal penetration. Anorectal melanomas must be staged by American Joint Committee on Cancer (AJCC) and/or TNM Classification of Malignant Tumours (TNM) criteria. As melanocytes can present with several shapes, sometimes the differential diagnosis with other tumors in this region may be difficult. Because of this, immunohistochemistry is mandatory to attain a precise diagnosis. This study is a report of 14 patients with anorectal melanoma, in whom histological examinations were remade and immunohistochemistry was performed with several markers for melanocytes and for other tumor cells of the anorectal region, properly establishing the diagnosis. The most rational surgery is the extended local resection, when the disease is restricted to the area or the abdominoperineal resection to advanced lesions. Regardless of the technique used, the results are always poor. The authors deny any efficacy of current radio and/or chemotherapy as part of treatment of anorectal melanoma. Target-therapy for metastatic disease has been considered a good strategy, but the results are still inconclusive.